Scholarly communication dan peran perpustakaan perguruan tinggi - Faizuddin Harliansyah (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2017)
This paper presents an explanation of the understanding, the scope of scholarly communication and its relationship with the publishing business related to serial crises, open access, and the potential extension of the role (extended role) of academic libraries. Currently the role of the library only focuses on user education programs (library instruction) which aims to disseminate the collection/resources library and its search strategy, especially those that are online or electronic. This role is only alluding with a small area of scholarly communication, namely discovery and dissemination. A wider role is information literacy programs, whose materials are packaged, expanded and aligned with the dynamics and scores of scholarly communication. This role is expected to spur engagement and contribution in developing a scholarly communication environment that is conducive to the development of science.